Rehabilitación respiratoria en pacientes adultos post trasplante pulmonar. - Cárdenas Obando, Joselin Uvaldina (2025)
This research focuses on Atelectasis, which refers to incomplete expansion of the lung due to collapse caused by intrapulmonary or extrapulmonary disorders, which can be general, segmental or subsegmental. Pulmonary atelectasis mainly affects children due to the anatomical characteristics of the airways. Respiratory physiotherapy is fundamental during atelectasis since it helps to minimize invasive processes through the application of bronchial clearance techniques, providing stabilization of respiratory frequency, heart rate, reducing the presence of adventitious pulmonary noises and oxygen saturation. The main goal is to analyze the benefits of respiratory rehabilitation techniques applied in children with pulmonary atelectasis with the purpose of improving quality of life, by means of a bibliographic review of randomized clinical trials. A bibliographic method was applied, since randomized controlled trials were collected from different scientific databases from which articles meeting the inclusion criteria and published between 2016 onwards were selected. The selected randomized controlled trials were assessed using the Physiotherapy Evidence Database (PEDro) scale. Twenty-five articles were selected that met the score equal to or greater than 6/10 same that are part of the research. In conclusion, physiotherapeutic intervention in children with pulmonary atelectasis helps to reduce hospitalization time, eliminates pulmonary obstruction, provides stability in pulmonary function, oxygen saturation, heart rate and respiratory rate, thus improving the quality of life of children.